A decade of population genetics studies of scleractinian corals: A systematic review. (January 2023) - Alvarado-Cerón, Viridiana; Muñiz-Castillo, Aarón Israel; León-Pech, María Geovana; Prada, Carlos; Arias-González, Jesús Ernesto
Abstract: Coral reefs are the most diverse marine ecosystems. However, coral cover has decreased worldwide due to natural disturbances, climate change, and local anthropogenic drivers. In recent decades, various genetic methods and molecular markers have been developed to assess genetic diversity, structure, and connectivity in different coral species to determine the vulnerability of their populations. This review aims to identify population genetic studies of scleractinian corals in the last decade (2010–2020), and the techniques and molecular markers used. Bibliometric analysis was conducted to identify journals and authors working in this field. We then calculated the number of genetic studies by species and ecoregion based on data obtained from 178 studies found in Scopus and Web of Science. Coral Reefs and Molecular Ecology were the main journals published population genetics studies, and microsatellites are the most widely used molecular markers. The Caribbean, Australian Barrier Reef, and South Kuroshio in Japan are among the ecoregions with the most population genetics data. In contrast, we found limited information about the Coral Triangle, a region with the highest biodiversity and key to coral reef conservation. Notably, only 117 (out of 1500 described) scleractinian coral species have genetic studies. This review emphasizes which coral species have been studied and highlights remaining gaps and locations where such data is critical for coral conservation. Highlights: Microsatellites are the most widely used markers in the study of genetic populations in scleractinian corals. In spite of 1500 species of scleractinian corals, only 117 species have been studied for population genetics. The two most studied ecoregions are those included in the Caribbean Sea and the Great Barrier Reef. The most studied species are those of the genus Acropora and Pocillopora.